A faunal treatment of the Megachile (Hymenoptera: Megachilidae) of Montana with a key for their identification - Pritchard, Zoe A.; Ivie, Michael A.; O’neill, Kevin M.; Delphia, Casey M. (Zootaxa, 2025)
We provide the first statewide inventory of the species of Megachile in Montana from 5,406 records, based on collecting efforts in 2019–2021 and physical specimen data from publications, natural history museums, private collections, and online data aggregators. We documented 35 species within the state, six of which are new state records: Megachile casadae Cockerell, Megachile centuncularis (Linnaeus), Megachile gentilis Cresson, Megachile mellitarsis Cresson, Megachile mendica Cresson, and Megachile snowi Mitchell. These were predicted to occur in Montana based on existing range data but had not been previously sampled due to limited prior collecting. We also confirmed Megachile dakotensis Mitchell and Megachile nevadensis Cresson to occur in eastern Montana, which had not been recorded in the state for 85 and 84 years respectively, most likely from a lack of collecting in their ranges. Based on published distributional data, we identified eight native species that might be found in the state with further collecting, as well as two introduced species that could reach Montana in the future. This work adds important Megachile species range data in North America, articulates several taxonomic challenges within the group, and will aid future identifications of Montana Megachile through a taxonomic key provided here.